IMPLEMENTASI MEANINGFULLY INSTRUCTIONAL DALAM PEMBELAJARAN JARAK JAUH DI ERA PANDEMI COVID-19 - Suhardin Suhardin (STKIP Muhammadiyah Bogor, 2020)
The some studies have discussed a lot about efforts to create meaningfully in a lesson. This article specifically proves that there are differences in the ability of students to explain verbally the meaning content of the letter Al-Jumuah verses 9-11 which are taught with contextual teaching learning strategies that emphasize meaningfully and collaborative learning strategies that emphasize collaboration and integration. The experiment research, by conducting two classes of learning on forty students, each class consisting of twenty students with the same ability. The data on the results of the students' ability to explain the contents of the letter Al-Jumuah verses 9-11 were analyzed with anova once or twice. The analysis resulted in the finding that there was a very significant difference in the students' ability to explain the contents of the verse. The concluded that contextual teaching learning which emphasizes meaningfully can have a very significant effect on students' ability to explain the content of the letter Al-Jumuah verses 9-11. The contextual teaching learning strategies that emphasize meaningfulness can be implemented in distance learning activities in the era of the Covid-19 pandemic.